First steps in building the Eurasian Latin Archive - Carbé, Emmanuela; Giannelli, Nicola (Qualitative and Quantitative Methods in Libraries; Vol 9 No 4 (2020): December Issue 2020, 2021)
The aim of the Eurasian Latin Archive (ELA) project is to build an open-access digital platform of Latin and multilingual texts from medieval and early modern times concerning East Asia, which will include a Digital library and tools for textual and semantic analysis.Beginning in March 2018, the start-up phase of ELA (DAS-MeMo, www.dasmemo.unisi.it) has been co-financed by Regione Toscana and involves the University of Siena, the IT company QuestIT, specialized in Artificial Intelligence, and the publisher Pacini, This article seeks to explain the workflow of the project and the first steps in building the prototype of the platform and adds some notes about further developments.